Tingkat konsumsi ikan di Kecamatan Selat Nasik Kabupaten Belitung - Kurniawan; Steven, Doni; Agusfianto, Jepri (Jurnal Sosial Ekonomi Perikanan, 2023)
The potential for fisheries in Selat Nasik sub-district is high. A total of 742 people work as main fishermen. The fish commodities found in Selat Nasik have high economic value and have even become export commodities to various countries. The Selat Nasik sub-district area has its own uniqueness, therefore researchers conducted an analysis related to the level of fish consumption. The purpose of this study was to measure the value of fish consumption levels in Selat Nasik District, Belitung Regency. The method used in the withdrawal of samples uses a random method using a random sheet. Sampling is done directly by looking for respondents in Selat Nasik Subdistrict, precisely in Selat Nasik Village and Suak Gual Village. This research was conducted in August 2023. This study uses data analysis methods, namely analysis of fish consumption levels and uses quantitative descriptive data analysis. The results of the analysis show that the level of fish consumption is 71.42 kg / capita, this result shows a high category compared to the level of fish consumption nationally. Researchers took data from the level of fish consumption in the Nasik Strait from 2020-2022 with data on the level of fish consumption in 2023. The results of the regression analysis show that the level of fish consumption in Selat Nasik District has decreased due to a slope value of -0.4713 and an intershape value of 1023.3. The decline in fish consumption levels is due to various factors such as uncertain fishing seasons and expensive fish prices. This is because fishermen erratically go to sea during high wind weather conditions so that the supply of fish is not fulfilled. In addition, there are also lock down policies that cause restrictions in the use of transportation, causing movement to be very tight or limited.